2019
DOI: 10.4103/jpbs.jpbs_76_19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of correlation of growth hormone receptor gene with tooth dimensions: A CBCT and genotyping study

Abstract: Aim: Assessment of root morphology, size, and amount of bone around tooth is essential before starting the orthodontic treatment. The present study aimed to assess the relationship between tooth dimensions with two gene variants of growth hormone (GH), namely rs6184 and rs6180. Materials and Methods: This study was conducted on 218 subjects (males: 104, females: 114) requiring orthodontic treatment. All underwent cone beam computed tomography (CBCT) scan for orthodontic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Among the various hormones and growth factors investigated, GH appears to be one of the most closely associated with dental maturity [ 8 ]. Recent studies have shown that GHR variants (rs6184 and rs6180) are associated with specific tooth and root dimensions [ 9 , 10 ], as well as with mandibular morphology [ 11 ]. Genetic polymorphisms in GHR (rs1509460) are also associated with developmental defects of enamel arguing for the GHR contribution to dental enamel synthesis and structure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various hormones and growth factors investigated, GH appears to be one of the most closely associated with dental maturity [ 8 ]. Recent studies have shown that GHR variants (rs6184 and rs6180) are associated with specific tooth and root dimensions [ 9 , 10 ], as well as with mandibular morphology [ 11 ]. Genetic polymorphisms in GHR (rs1509460) are also associated with developmental defects of enamel arguing for the GHR contribution to dental enamel synthesis and structure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data demonstrate the involvement of GH and GHR in physiological development of the dento-alveolar complex in addition to their well-known consequences when GH levels are deregulated notably on mandibular growth (prognathism or retrognathism). However, the beneficial or detrimental consequences of deregulated GH secretion on dento-alveolar complex are controversial, as reported recently for acromegaly, which does not appear to induce generalized hypertrophy of the gingiva or hypercementosis, but could protect from a severe periodontal disease by conferring more robust periodontal tissues [ 10 , 13 ] due to an increase in the levels of protective molecules such as bone morphogenetic protein 2 (BMP2) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CBCT is widely in orthodontic research and diagnostics [43,44]. At the same time, this method provides access to inner dental morphology and roots which are concealed under bone tissue [45][46][47]. The increasing reliance on micro-computed tomography, especially in the recent two decades, allows for obtaining accurate and detailed images of outer and inner structures of teeth.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Actually different techniques can be used for measurements. Some researchers are interested in measuring the whole tooth dimensions (Yu et al, 2019), (Shinde et al, 2019), (Rathmann et al, 2019), however, probably the most widely used and regulated are measurements of crowns in buccal-lingual and mesial-distal dimensions, which can be used independently (Priyambadha and Artaria, 2016), (More et al, 2017) or in combination with other techniques (Xiao et al, 2014), (Glantz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%